Nursing professionals’ attitudes toward biostatistics: an international web-based survey - Ocakoğlu, Gökhan; Kaya, Mehmet Onur; Can, Fatma Ezgi; Atış, Sema; Macunluoğlu, Aslı Ceren (The European Research Journal, 2019)
Objective: The present study, an international web-based survey, was focused on four aims: to obtain nursing professional’s self-reported statistical knowledge levels and how this knowledge varies by research area, to investigate and specify when biostatistics courses should be taught in nursing education and to identify the key statistical methods relevant to nursing education. Methods: A total of 448 nursing professionals from five continents and 52 countries participated in our study. For the data comparison, the Kruskal-Wallis test, the Mann-Whitney U test, the Pearson Chi Square and Fisher-Freeman-Halton tests were applied. Results: The results indicate that while nursing professionals place an emphasis on biostatistics education, the majority state that biostatistics education should be taken both at the undergraduate and postgraduate level and the participants also believe that taking a biostatistics course is useful for their occupation. A biostatistics education should also emphasize the necessity of consulting to a biostatistician when planning a study. Conclusion: Our study provides information regarding self-reported levels of biostatistical knowledge of nursing professionals by research area and academic position, and provides guidance regarding the ideal semester for administering a biostatistics course.